Time and context shaping the transition from out-of-home care to adulthoodin Portugal - Artamonova, A. (2020)
The difficulties that modern care leavers face on the way to independence are the focus of many studies. The present research illustrates how time and context - operationalised through belonging to different generations, from the previous century to today – has shaped care leavers’ pathways to adulthood in Portugal. To trace these pathways, ten care leavers were selected based on purposeful sampling and snowball methods. To reveal the factors that indicate care leavers’ better life outcomes, interviews with seven experts working with this vulnerable population group were organised. The pathways of male informants look “normal”, even thriving, when compared with the trajectories of the general population of Portugal in the second half of the 20th century, while the experiences of female care leavers sound somewhat traumatising. The timing and sequence of the young cohorts’ transition to adulthood events does not look aberrant compared to the general population. The various factors that determine a care leaver's better life outcomes emerged as access to the tangible and intangible resources needed to generate human and social capital, and personal agency. Care leavers from older cohorts were empowered by means of education and the support of former residents of out-of-home care institutions. Women from older cohorts could receive education but, due to the social context, they were not expected to build careers. The educational opportunities given to them were very basic and did not afford them the confidence to deal with adversity. Care leavers from younger cohorts seem to lose the advantage of competitive education and the sense of belonging to a large and powerful childcare institution due to the democratisation of the education system and de-institutionalisation of residential care in the country. However, they can stay in care longer, gain practical skills for independent living and benefit from the personalised support of professionals to deal with adversity.